Philosophy a critique - Hasan, Syed Zafarul (Institue of Islamic Culture, 1988)
The summing of the author's views in his maturest years. He was one of the great original philosophers that this part of the world has produced in this century. Grounded deep into the Kantian tradition of thought he has articulated in this book his thoughts developed over years of contemplation.